MINERAL FORMS OF TUNGSTEN AT THE POROKHOVSKOE AND YUGO-KONEVSKOE DEPOSITS (SOUTH URALS) - D.A. Rogov; E.V. Belogub; K.A. Novoselov; M.A. Rassomakhin; R.R. Irmakov; A.E. Chugaev (Минералогия)
The ore hand specimens and technological ore samples from the Porokhovskoe and Yugo-Konevskoe W greisen deposits in the South Urals are studied. The major W minerals of primary ores at both deposits include hübnerite and scheelite. The secondary and accessory minerals are pyrite, chalcopyrite and molybdenite, rare minerals include sphalerite, galena, bismuthinite, aikinite, unidentified chalcogenides and sulfosalts, magnetite, rutile, ilmenite, titanite and columbite. The veins are mainly composed of quartz and muscovite with subordinate calcite, dolomite and fluorite, rare chlorite and amphibole and accessory zircon, apatite and uraninite. No zonation in the distribution of wolframite with various Fe content is identified relative to the Yugo-Konevsky granite pluton, however, wolframite of the Northern area of the Porokhovskoe deposit is enriched in Fe compared to that of the Central area and Yugo-Konevskoe deposit. In addition to veined wolframite and scheelite, the oxidized ores also contain Fe and Mn oxyhydroxides, malachite, pyromorphite and bromargyrite. Tungsten is part of Mn and Fe oxyhydroxides, which replace wolframite and less often sulfides. The WO3 content of pseudomorphic Mn and Fe oxyhydroxides after hübnerite reaches 18 wt. %. Single grains of stolzite and russellite are found. According to the results of phase chemical analysis of technological samples, the amount of tungstite in oxidized ores is minor, therefore all ores of both deposits were ascribed to primary type.